General college chemistry - Keenan, Charles W.; Kleinfelter, Donald C.; Wood, Jesse H. (San Francisco, California : Harper & Row Publishers, Inc., 1980)
This new edition of General College Chemistry, like its predecessors, presents an introduction to chemistry for the student who seeks a firm foundation in the subject. The coverage is broad, but it is also deep in certain areas. The subjects that are emphasized-such as atomic and molecular structure, chemical bonding, acids and bases, equilibrium, and the periodic relationships of elements-are fundamental to many disciplines other than chemistry. This text is designed not only for the science major, but also for the person who wants a cultural understanding of the chemical way of looking at the world around us.
Chapter 1. Preview of descriptive and theoretical chemistry -- Chapter 2. Chemical equations; Stoichiometry -- Chapter 3. Structures of atoms; periodic relationships -- Chapter 4. Atomic spectroscopy; modern electronic theory -- Chapter 5. Chemical compounds -- Chapter 6. Theories of the covalent bond -- Chapter 7. The gaseous state -- Chapter 8. Changes of state: Liquids and solid -- Chapter 9. the chemical behavior of hydrogen, oxygen and water -- Chapter 10. Solutions, electrolytes and non electrolytes -- Chapter 11. Acids and bases -- Chapter 12. Properties of solutions; the colloidal state -- Chapter 13. Thermochemistry: thermodynamics -- Chapter 14. Chemical kinetics -- Chapter 15. Chemical equilibria -- Chapter 16. Ionic equilibria I: Solutions of acids and bases -- Chapter 17. Ionic equilibria II: Solubility and solubility product -- Chapter 19. Ionic equilibria III: Redox and electrochemistry -- Chapter 20. Molecular spectroscopy and molecular structure -- Chapter21. Metals I: properties and production -- Chapter 22. Metal II: More about transition metals -- Chapter 23. Groups VIIA and VIIIA: the halogens and noble gases -- Chapter 24. Groups VIA and VA: the sulfur family and nitrogen family -- Chapter 25. Carbos, silicon and boron -- Chapter 26. Organic chemistry -- Chapter 27. Complex derivatives of hydrocarbons; biochemistry
Includes index.
Keywords: CHEMISTRY